Implementasi E-Voting dalam Pemilihan Wali Nagari Balingka di Kecamatan IV Koto Kabupaten Agam Tahun 2023 - Afifah Yusuf; Ratna Dewi (Al-Manar Journal of Economic and Social Studies, 2024)
This research was conducted in Nagari Balingka, IV Koto District, Agam Regency. The aim of this research was to determine the implementation of e-voting in the election of the guardian of Nagari Balingka in IV Koto District, Agam Regency in 2023. This research used a qualitative descriptive method with the determination of informants carried out through purposive sampling technique. Data collection was carried out through observation, interviews and documentation. The results of the research show that the implementation of e-voting in the election of Mayor of Nagari Balingka in District IV Koto, Agam Regency in 2023 has been carried out quite well, even though there are obstacles in the way. This research identifies four indicators, namely communication, resources, disposition and bureaucratic structure. The implementation of e-voting in the election of Balingka village guardian in IV Koto District, Agam Regency in 2023 has not yet reached optimal levels. Some of the obstacles encountered in the process of selecting nagari mayors using e-voting are the obstacles among people who are still unfamiliar with technical matters and regulations regarding election procedures using e-voting tools, especially the elderly, because the socialization that was carried out was not carried out thoroughly, only that socialization was carried out time for the nomination of nagari guardians and socialization is only given to TPS officers.